Hydro-sedimentary processes of a shallow tropical estuary under Amazon influence. The Mahury Estuary, French Guiana. (5th April 2017) - Orseau, Sylvain; Lesourd, Sandric; Huybrechts, Nicolas; Gardel, Antoine
Abstract: Along the Guianas coast, coastal dynamic is characterized by the migration of mud banks originating from the Amazon. This singular feature affects the dynamic and the morphology of local estuaries and can induce rapid bathymetric evolution in lower estuaries. Since 2012, the navigation channel of the Mahury Estuary (French Guiana) is enduring a severe siltation whose origin comes from a mud bank crossing the estuary mouth. This study aims to determine how the migration of a mud bank through an estuary mouth could influence the transport and fluxes in the estuary. Field measurements were performed over a year with the monitoring of the salt intrusion length, mooring surveys during spring-neap cycles and shipboard profiling surveys during semi-diurnal cycles. Salt intrusion lengths underline a significant seasonal variation characterized by the transition from a steady-state length during high river discharge and a wide range of lengths with the tidal range during low to moderate river discharge. During the rainy season, measurements indicate a fluvial-dominated condition with low suspended-sediment concentrations most of the semi-diurnal cycle. Residual sediment fluxes are usually seaward excepted when river discharge is below seasonal average. During the dry season, maximum suspended-sediment concentrations are higher in the middle part of the estuary. Residual sediment fluxes are landward along the estuary and stronger during neap tides in the estuary mouth and few kilometers upstream. In this area, a persistent density stratification traps sediments in the bottom layer and generates a gravitational circulation during neap tides, which enhances landward transports up to 2.56 t m −1 over a semi-diurnal cycle. In the middle estuary, landward fluxes are most significant during the dry season and also during the rainy season when the river discharge is below the seasonal average. Although this study includes temporal and spatial limitations, it underlines significant mud inflows in the middle part of the estuary during low to moderate river discharges. Comparison with old data suggests higher sediment loads in the estuary during the migration of a mud bank but must be confirmed by further studies during the interbank period. Highlights: Seasonal variation of river discharge creates a well-marked cycle of salinity and SPM distribution. Resuspension by tidal currents is the main mechanism of SPM dynamics. Suspended-sediment Alux is dominated by the non-tidal advective component. Gravitational circulation favors mud inAlows during the dry season.